PERBEDAAN PEMAHAMAN KONSEP FISIKA SISWA MELALUI MODEL PROBLEM-BASED LEARNING DAN PEMBELAJARAN INTERAKTIF: (Differences in Students' Understanding of Physics Concepts through the Problem-based Learning Model and Concept-based Interactive Learning) - Badu, Tri Kurnia; Ikbal, Muh. Syihab (Uniqbu Journal of Exact Sciences, 2020)
This research is a Quasi-experimental research which aims to determine the level of understanding of the physics concepts of students taught by the Problem Based Learning model in class XI students of SMA Negeri 1 Bontonompo, to determine the level of understanding of the physics concepts of students who are taught using the Concept-Based Interactive learning model in class students. XI SMA Negeri 1 Bontonompo, to find out the difference in understanding the concepts of physics between students taught by the Problem Based Learning learning model and students taught with the Concept-Based Interactive Learning model in class XI students of SMA Negeri 1 Bontonompo. The design used in this study is "The matching only Posttest only control group design". The population in this study were 247 students of class XI IPA at SMA Negeri 1 Bontonompo in the academic year 2015/2016, consisting of 8 classes. The sample in this study amounted to 30 people spread in two classes obtained through purposive sampling with matching techniques. The instruments used in this research are the concept understanding test instrument, observation sheets and learning tools (RPP). The results showed that there was a significant difference in understanding the concept of physics between students who were taught using the Problem Based Learning model and students who were taught using the Concept-Based Interactive Learning model in class XI IPA 6 and class XI IPA 5. This is shown by the tcount value of 5.05 and the ttable value of 2.04, then tcount> ttable so that H0 is rejected and H1 is accepted.